2014
DOI: 10.1007/s10461-014-0797-9
|View full text |Cite
|
Sign up to set email alerts
|

Drug Users’ Willingness to Encourage Social, Sexual, and Drug Network Members to Receive an HIV Vaccine: A Social Network Analysis

Abstract: This study examined feasibility of peer-based promotion of HIV vaccination and dyadic correlates to vaccine encouragement in risk- and non-risk networks of drug users (n = 433) in the US. Data were collected on HIV vaccine attitudes, risk compensation intentions, likelihood of encouraging vaccination, and recent (past 6 months) risk (i.e. involving sex and/or injecting drugs) and non-risk (i.e. involving co-usage of noninjected drugs and/or social support) relationships. Willingness to encourage HIV vaccinatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 39 publications
1
6
0
Order By: Relevance
“…Interestingly, similar research in this setting revealed that men were somewhat less willing to encourage HIV vaccination among peers but more likely to receive encouragement to get vaccinated (37). Together, these findings highlight the instrumental role that women may play in disseminating positive vaccine messages among their drug-using peers.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Interestingly, similar research in this setting revealed that men were somewhat less willing to encourage HIV vaccination among peers but more likely to receive encouragement to get vaccinated (37). Together, these findings highlight the instrumental role that women may play in disseminating positive vaccine messages among their drug-using peers.…”
Section: Discussionmentioning
confidence: 96%
“…In addition, participants were asked only about their WEP among drug-using peers in general and not on a partner-by-partner basis. Given previous research that suggests selectivity in vaccine communication among social, sexual and drug network members (37), future studies should examine not only if participants will encourage trial participation but to whom . Nevertheless, it is notable that indication of strong willingness to encourage trial participation among peers was present in nearly half the sample.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sample demographic and behavioral characteristics have been reported elsewhere (Young, DiClemente, et al, 2014a, 2014b; Young, Halgin, et al, 2014). Participants were predominantly White (94%), male (55%), and unmarried (75%).…”
Section: Resultsmentioning
confidence: 99%
“…A questionnaire to examine attitudes toward HIV vaccination and risk compensation intent was administered during participants’ 24-month assessment; the data from this questionnaire were used for the analyses presented below. Details on the HIV vaccine survey methods have been described previously (Young, DiClemente, Halgin, Sterk, & Havens, 2014a, 2014b; Young, Halgin, et al, 2014). All participants tested HIV negative at the 24-month visit.…”
Section: Methodsmentioning
confidence: 99%